ANALISIS PENYERAPAN TENAGA KERJA PADA INDUSTRI ROKOK DI KABUPATEN KUDUS TAHUN 1993-2010 - Romadhansya Indra Setiyadi; Purbayu Budi Santosa (Diponegoro Journal of Economics, 2013)
Unemployment is a labor issue that currently has reached a critical condition. One attempt to reduce unemployment is to develop sectors that can create jobs. The industrial sector is one sector that has a noticeable role in employment. In Kudus Regency, one of the industries that have an important role in employment is the cigarette industry. This study aims to analyze the factors affecting employment in the cigarette industry in Kudus Regency in 1993-2010. This study uses time series data years 1993-2010 were analyzed using multiple regression methods. The results of the analysis showed that the variable number of firms has a positive and significant effect on employment industry. Variable wages has a positive and signifcant effect on employment industry. PDRB has a positive and not significant effect on employment industry. Rate investment and Dummy variable have a negative and not significant effect on employment of the cigarette industry in the Kudus Regency.